Sensory Mapping Using Flash Profile and Check-All-That-Apply Methods to Evaluate Flavor of White Basic Seasoning in Different Cooking Methods - Rully, Rizal Dziki; Fibri, Dwi Larasatie Nur; Supriyadi, Supriyadi (agriTECH, 2026)
White basic seasoning (bumbu dasar putih) is an important component of traditional Indonesian cuisine that contributes significantly to the flavor of many dishes. Therefore, this study aimed to characterize the sensory profile of white basic seasoning prepared with four cooking methods, including boiling, steaming, frying, and roasting, using two rapid sensory methods known as Flash Profile (FP) and Check-All-That-Apply (CATA). A total of 40 untrained panelists evaluated the samples of seasoned tempeh as model matrix, and 17 sensory attributes were generated through a Focus Group Discussion (FGD). FP data were analyzed using Generalized Procrustes Analysis (GPA), while CATA data were analyzed with Cochran’s Q test followed by Correspondence Analysis (CA). The results showed that cooking methods significantly influenced the intensity and diversity of flavor attributes. Sensory mapping from FP indicated that the first two dimensions explained 41.97% of the total variance, distinguishing samples based on attributes such as sour, smoky, bitter, sweet, mild, and bland. Samples processed by roasting and frying were associated with intense attributes including roasted, smoky, nutty, and bitter, while boiling and steaming methods produced fresher and milder attributes. Similarly, CA of the CATA data clarified a large proportion of sensory variation (F1 = 56.03%; F2 = 15.39%), where boiled samples were associated with sweet, earthy, and mild attributes. Roasted samples were connected to pungent, roasted, bitter, and astringent attributes. In conclusion, FP effectively identified differentiating attributes among samples, and CATA captured panelists’ perceptions of dominant flavor attributes.